Effect of Buffer Layer selection on Perovskite-Based Solar Cell Efficiency: A Simulation Study Using OghmaNano Software - Mourched, B; Sawaya , S; Abdallah, M; Abboud, N (The International Journal of Multiphysics, 2023)
This simulation paper investigates the impact of incorporating three different buffer layers (CZTSE, CZTS, and CZS) on the efficiency of two different types of perovskite absorber layers (MAPbCl3 and MAGeI3) in a solar cell using the OghmaNano software. The absorber thickness is optimized for maximum efficiency, and then each type of buffer layer is optimized for further efficiency gains. Results show that MAGeI3 has higher efficiency values compared to MAPbCl3. Moreover, the CZS buffer layer demonstrates a remarkable increase in efficiency compared to CZTS and CZTSe buffer layers, with a difference of up to 23.35% for MAPbCl3 and 6.8% for MAGeI3. This study highlights the importance of buffer layer selection and optimization for achieving higher solar cell efficiency.